Leveraging Pan-Africanism to Fight French Neocolonialism in Francophone Africa: A Study of the Cameroonian Audio-Visual Media and Intelligentsia - Floribert Patrick C. Endong (Asian Journal of Media and Communication, 2022)
The persistence of French neo-colonialism has motivated the emergence of new and very aggressive forms of pan-Africanism in most – nay all – Francophone African countries. Indeed, many Francophobic pressure groups operating in Francophone African countries have sought to resist French neo-colonialism in their countries by mobilizing forms of pan-Africanism, which to a great extent, are xenophobic and disruptive to France’s diplomacy in specific Francophone African countries. In Cameroon, for instance, several so-called pan-African media initiatives, such as Afrique Media, have resorted to a very combative – but professionally problematic – form of journalism called ‘journalism of opinion’ to denounce Western political imperialism and contribute in no small measure, to the fight against Western (and particularly French) neo-colonialism in Cameroon. This paper seeks to illustrate the above phenomenon hinging on secondary sources and critical observations. Specifically, the paper explores indexes of French neo-colonialism in Cameroon and examines how the Cameroonian intelligentsia, in general and specific pan-African media houses in the countries in particular, have sought to combat this French neo-colonialism.